Les relations mère-enfant dans le corpus homérique - Susana Reboreda Morillo (Cahiers Mondes Anciens)
This investigation centres on the idea that the Homeric texts transmit some pieces of information on the greek conception of maternity. I am conscious that my task presents many difficulties, beginning for the famous “Homeric question”. My proposal is to collect all the evidence of the relation mother/son/daughter following, as far as possible, the order of the stages of growth, from the most tender infancy up to the maturity; this choice will force me to approach the Iliade or the Odyssey depending on the subject that I will tackle. The analyses will include also mentions to both the human and the divine world; this liberty is possible because I always focus on human children, sometimes of human mothers, sometimes of divine mothers. The feelings of some and others can be comparable because they share the fact that their children are mortal.